2020
DOI: 10.1093/nsr/nwaa286
|View full text |Cite
|
Sign up to set email alerts
|

Using bio-orthogonally catalyzed lethality strategy to generate mitochondria-targeting anti-tumor metallodrugs in vitro and in vivo

Abstract: Synthetic lethality was proposed nearly a century ago by geneticists and recently applied to develop precision anticancer therapies. To exploit the synthetic lethality concept in the design of chemical anticancer agents, we developed a bioorthogonally catalyzed lethality (BCL) strategy to generate targeting antitumor metallodrugs both in vitro and in vivo. Metallodrug Ru-rhein was generated from two nontoxic species Ru-N3 and rhein-alkyne  via exclusive endogenous copper-catalyzed azide alkyne cycloaddition (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…[ 17 ] Other metal complexes tended to locate in mitochondria and induced caspase‐dependent apoptosis by mitochondrial damage, cellular ATP depletion, mitochondrial respiratory inhibition, and elevated production of reactive oxygen species (ROS). [ 18‐19 ] Furthermore, some metal complexes escaped and migrated to other organelles once stimulated by photoirradiation to produce ROS. [ 20 ] Therefore, such targeted luminescent metal complexes provide a structural foundation for the further design and optimization of metallodrugs.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 17 ] Other metal complexes tended to locate in mitochondria and induced caspase‐dependent apoptosis by mitochondrial damage, cellular ATP depletion, mitochondrial respiratory inhibition, and elevated production of reactive oxygen species (ROS). [ 18‐19 ] Furthermore, some metal complexes escaped and migrated to other organelles once stimulated by photoirradiation to produce ROS. [ 20 ] Therefore, such targeted luminescent metal complexes provide a structural foundation for the further design and optimization of metallodrugs.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…They have all been verified at the cellular level. Splenocytes, natural killer (NK) cells, human liver cancer cells (HepG2) [ 77 ], human gastric cancer cells (AGS), human colorectal cancer cells (HCT) and human non-small-cell lung cancer calls (A549) [ 77 , 78 ] were selected as the experimental models to verify the anti-tumor activity of Fructus Malvae. Splenocyte proliferation ability, natural killer (NK) cell activity, AGS cell apoptosis percentage, and the expression of the apoptosis proteins PARP, Cleaved APRP, Caspase-3, Cleaved Caspase-3, Bcl-2, Bax, β-actin, etc.…”
Section: Research Progress On Pharmacological Activitymentioning
confidence: 99%
“…37−39 Instead of introducing exogenous Cu, copper ions in cancer cells were used as a catalyst of CuAAC for the synthesis of an anti-tumor metallodrug. 40 However, recent studies have reported that oncogenes could drive the fluctuation of the intracellular glutathione metabolism, thus inducing a labile Cu(I) deficiency. 41 The intratumoral Cu(I) is far from sufficient to efficiently catalyze the CuAAC reaction.…”
Section: ■ Introductionmentioning
confidence: 99%